COLLABORATIVE LEARNING OR INDEPENDENT LEARNING PREFERENCES IN ACADEMIC ENVIRONMENTS - Ecaterina Sarah FRĂSINEANU (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2025)
Our research on the preferences for collaborative or independent academic learning has helped us identify the complexity of the factors and reasons that lead to such choices. Learners combine the two modalities, in terms of their advantages and disadvantages, and although, declaratively, they are open to collaborative learning, in practice, they are more into independent learning. The responses collected indicated the need for the teachers to be, in turn, the promoters of collaborative learning, through practice and encouragement, both in the face-to-face and online learning systems. For pedagogical reasons, we considered that for the 122 undergraduate and graduate students preparing to be teachers, included in our sample, the investigative methods such as the questionnaire-based survey and the focus group are non-invasive methods, through which we were able to outline a profile dominated, in most cases, by independent learning or the combined variant, which alternates situations of independence and collaborative cases. Our findings highlighted that preferences are determined by a series of contextual factors: the possibilities of attentional concentration, the access to resources, the personal rhythms, the pursuit of efficiency, personality types, the learning planning skills, the need for evaluative feedback, the conceptions about the development of the creative process, the degree of social trust, the way of public expression, the teachers' practices.